The Importance of Teaching Vocabulary - Akbarova Iroda Akramovna (Zien Journals, 2022)
This article outlines that vocabulary knowledge is not something that can ever be fully mastered; it is something that expands and deepens over the course of a lifetime. The purpose of the article is to find out the appropriate principles and methods for teaching vocabulary. It is devoted to the theory of vocabulary teaching and present techniques in the classroom using different approach for teaching vocabulary. The main goal is to assess the relationship between teaching approach and students’ final knowledge, focusing on vocabulary load.
Keywords: Teaching vocabulary; Word cards; Word association; Visual techniques